UPAYA MENGATASI PENYALAHGUNAAN MEDIA SOSIAL MENGGUNAKAN PENDEKATAN KONSELING CLIENT CENTERED PADA SISWA SMA DI PANTI ASUHAN YATIM PUTRI AISYIYAH II SURAKARTA TAHUN 2020/2021 - Karima, Naila (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
The purpose of this study to overcome the impact of social media abuse by high school students at The Aiyiyah II Surakarta Orphanage in everyday life. Thesis. Surakarta: Faculty of Teacher Training and Education Slamet Riyadi University, November 2021.The research method used is the PTBK method which is research conducted by BK teachers or counselors in the school or BK room where he serves with pressure on refinement or improvement of the process and practical counseling. In this study using the PTBK approach consisting of 2 or more cycles and each cycle consists of 4 main activities with name : planning, action, observation, reflection. The result of study of changes found that the behavior of social media abuse toward not abusing social media in high school students in the Pre Cycle found an understanding level of (40%), then after the first cycle found resulta (60%) which were categorized as moderate if there was a reduction in abuse. Social media for students who abuse,the result in cylcle II found the level of understanding of MY students (86,2%) and FR students (85%) which was categorized as very successful if students did not abuse social media. Thus,it can be concluded that from pre-cycle to cycle I ant then to cycle II, it shows a change for the better. Keywords : Overcoming Social Media Abuse, Client-Centered Counseling, Orphanages.